Self-Regulated Learning Siswa SMP N 1 Lubuk Alung - Haryati Dahlia; Asmidir Ilyas (Jurnal Neo Konseling, 2021)
This study aims to describe the self-regulated learning of SMP Negeri 1 Lubuk Alung students. This study uses a quantitative approach with descriptive research methods with a sample size of 268 students. Sampling using proportional random sampling technique. The instrument used was a self-regulated learning questionnaire, a Likert scale model. This study measures self-regulated learning which includes: cognitive, motivation and behavior. The findings of this study reveal: (1) on average the overall students of SMP Negeri 1 Lubuk Alung have self-regulated learning in the high category (69.81%), (2) the overall average grade VII students of SMP Negeri 1 Lubuk Alung have self-regulated learning. -regulated learning with a high category (70.41%), (3) the overall average grade VIII students of SMP Negeri 1 Lubuk Alung have self-regulated learning with a high category (69.09%), (4) the overall average grade students IX SMP Negeri 1 Lubuk Alung has a high category of self-regulated learning (69.92%)